2020
DOI: 10.1038/s12276-020-0387-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 suppresses hepatocyte proliferation in fulminant hepatic failure through increased recruitment of EZH2 to the LATS2 promoter region and promotion of H3K27me3 methylation

Abstract: Fulminant hepatic failure (FHF) refers to the rapid development of severe acute liver injury with impaired synthetic function and encephalopathy in people with normal liver or well-compensated liver disease. This study aimed to investigate the function of long noncoding RNA (lncRNA) nuclear-enriched abundant transcript 1 (NEAT1) on the proliferation and apoptosis of hepatocytes in FHF. Our results revealed that lncRNA NEAT1 was upregulated in cell and animal models of FHF induced by D-galactosamine (D-GalN)/li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…For instance, LINC00114 suppressed miR-133b expression via EZH2/DNMT1-mediated methylation of its promoter region and facilitated colorectal cancer development [16]. Long noncoding RNA NEAT1 (nuclear-enriched abundant transcript 1) inhibited hepatocyte proliferation in fulminant hepatic failure via strengthened recruitment of EZH2 to the LATS2 (large tumor-suppressor kinase 2) promoter region [18]. Importantly, SNHG1 was also proved to interact with EZH2 and inhibit CDKN2B (cyclin-dependent kinase inhibitor 2B) and CDKN1A (cyclin-dependent kinase inhibitor 1A) transcription [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, LINC00114 suppressed miR-133b expression via EZH2/DNMT1-mediated methylation of its promoter region and facilitated colorectal cancer development [16]. Long noncoding RNA NEAT1 (nuclear-enriched abundant transcript 1) inhibited hepatocyte proliferation in fulminant hepatic failure via strengthened recruitment of EZH2 to the LATS2 (large tumor-suppressor kinase 2) promoter region [18]. Importantly, SNHG1 was also proved to interact with EZH2 and inhibit CDKN2B (cyclin-dependent kinase inhibitor 2B) and CDKN1A (cyclin-dependent kinase inhibitor 1A) transcription [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Many lncRNAs regulate the expression of local or distal genes and contribute to malignant biological behaviors of cancer cells. 33 , 34 In this study, we conducted RIP experiments and found that linc00665 can bind to EZH2 in NSCLC cells. RNA-seq analysis of H1299 cells with linc00665 expression knocked down suggested that the tumor suppressor gene CDKN1C is a downstream regulatory gene of linc00665 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, overexpression of NEAT1 could inhibit large tumour‐suppressor kinase 2 (LATS2) expression by recruiting enhancer of EZH2 to its promoter, which can suppress LAST2 expression by methylation of H3K27. Further mechanistic studies demonstrated that NEAT1 indirectly blocked the activation and nucleus entry of Yes‐associated protein1 (YAP1) via LAST2, which contributes to P73 binding to YAP1 and apoptosis mediated by P73 113 …”
Section: Role Of Neat1 In Liver Diseasesmentioning
confidence: 99%